"It's about how we do it, not if we do it". Nurses' experiences with implicit rationing of nursing care in acute care hospitals: A descriptive qualitative study. (September 2020) - Mantovan, Franco; Muzzana, Chiara; Schubert, Maria; Ausserhofer, Dietmar
Abstract: Background: The phenomenon of unfinished nursing care is gaining increasing interest among nursing researchers. While survey studies on the underlying concepts, e.g., implicit rationing of nursing care, revealed frequencies, antecedents and consequences, little is known about how nurses experience care rationing in clinical practice. Objectives: The aim of this study was to explore nurses' experiences with implicit rationing of nursing care in acute-care hospitals. Design: We conducted a qualitative study using interpretive description methodology. Methods: Using a convenience sample of 31 frontline nurses (i.e., registered nurses, nurse assistants) and 19 ward nurse managers from acute care units in seven hospitals in [Blinded], eight semi-structured focus group interviews were conducted, transcribed verbatim and analyzed via thematic analysis. Results: Our findings indicate three interconnected themes: (a) maintaining stability within complexity; (b) applying strategies to limit rationing; and (c) nursing care between ideal and reality. According to study participants, implicit rationing of nursing care results when nurses cannot otherwise maintain stability for their patients and their units. Nurses reported several strategies, including postponing tasks or reducing quality, to prevent or limit rationing. Rationing accentuates the gap between ideal nursing care and day-to-day practice. Conclusions: In absence of guidelines on implicit rationing of nursing care nurses rely on intuitive and situational processes of decision-making and priority setting. Technical activities addressing patients' instability receive higher priority than relational ones. As quality may be an earlier casualty of implicit rationing than quantity, it challenges us to broaden the current focus of how care rationing manifests. In addition to encouraging open discourse on implicit and non-transparent rationing at all organizational levels, this qualitative study provides new insights that will inform the development and implementation of interventions to support nurses' priority setting and ultimately to limit rationing of nursing care.